Advances in Natech research: An overview. (May 2019) - Cruz, Ana Maria; Suarez-Paba, Maria Camila
Abstract: Natural hazard triggered technological accidents involving the releases of hazardous materials (hazmat) are known as Natechs. These types of complex events were studied for the first time at the end of the 1970s, and in recent years have gained importance due to their increasing trend. This paper presents an overview of the advances in Natech research right up to 2018. The paper shows how Natech research was first focused on earthquakes as the main triggering event, and later shifted to hydrometeorological hazards, multi-hazard studies and cross cutting issues. The paper identifies current challenges and research gaps in both the theoretical understanding and the practical implementation and streamlining of Natech risk reduction in chemical accident regulations, and proposes a way forward for future research. Some of the main findings include the importance that interdisciplinary approaches have gained in the Natech context and the need for analyzing Natech accidents' long-term effects. Overall, increased contributions have supported Natech risk assessment and management development, but efforts are needed to enhance risk treatment, risk reduction, and risk communication strategies, without neglecting Natech education and awareness raising.